Fecal Lactoferrin: Reliable Biomarker for Intestinal Inflammation in Pediatric IBD. (24th May 2015) - Buderus, Stephan; Boone, James H.; Lentze, Michael J.
Abstract : Background . Optimal management of pediatric patients with inflammatory bowel disease (IBD) requires early diagnosis. Aim of the study is to compare fecal lactoferrin (FL) as biomarker of intestinal inflammation to CRP in pediatric patients with new-onset IBD. Methods . FL was measured by ELISA in stool specimens collected prior to endoscopy for IBD (IBD-SCAN; TechLab, Blacksburg; normal < 7.3 µ g/g feces). CRP was detected in serum (normal < 5 mg/L). Three patient groups were determined: n = 21 (mean age 13.2) with Crohn's disease (CD), n = 15 (mean age 10.9) with ulcerative colitis (UC), and n = 20 (mean age 11.9) in whom IBD was ruled out. In CD patients the endoscopic severity score SES-CD was correlated with the FL levels. Results . (Mean ± SEM) . CRP levels were 27.18 ± 4.2 for CD-cases, 20.8 ± 9.5 for UC, and 0.24 ± 0.06 for non-IBD patients. FL levels were 313.6 ± 46.4 in CD, 370.7 ± 46.9 in UC, and 1.3 ± 0.5 in non-IBD patients. Sensitivity of CRP to detect IBD was 75% with specificity of 100%, positive predictive value of 100%, and negative predictive value of 69%. Sensitivity of FL was 100% with specificity of 95%, positive predictive value of 97.3%, and negative predictive value of 100%. In CD, FL levels correlated positively (R 2 = 0.42 ) with disease severity as judged by the SES-CD. Conclusions . Elevated FL corresponds to intestinal inflammation, even in patients with normal CRP. With high probability, normal FL excludes intestinal inflammation.